Temozolomide antagonizes oncolytic immunovirotherapy in glioblastoma - Dipongkor Saha; Samuel D Rabkin; Robert L Martuza (Journal for ImmunoTherapy of Cancer)
Background Temozolomide (TMZ) chemotherapy is a current standard of care for glioblastoma (GBM), however it has only extended overall survival by a few months. Because it also modulates the immune system, both beneficially and negatively, understanding how TMZ interacts with immunotherapeutics is important. Oncolytic herpes simplex virus (oHSV) is a new class of cancer therapeutic with both cytotoxic and immunostimulatory activities. Here, we examine the combination of TMZ and an oHSV encoding murine interleukin 12, G47Δ-mIL12, in a mouse immunocompetent GBM model generated from non-immunogenic 005 GBM stem-like cells (GSCs.Methods We first investigated the cytotoxic effects of TMZ and/or G47Δ-IL12 treatments in vitro, and then the antitumor effects of combination therapy in vivo in orthotopically implanted 005 GSC-derived brain tumors. To improve TMZ sensitivity, O6-methylguanine DNA methyltransferase (MGMT) was inhibited. The effects of TMZ on immune cells were evaluated by flow cytometery and immunohistochemistry.Results The combination of TMZ+G47Δ-IL12 kills 005 GSCs in vitro better than single treatments. However, TMZ does not improve the survival of orthotopic tumor-bearing mice treated with G47Δ-IL12, but rather can abrogate the beneficial effects of G47Δ-IL12 when the two are given concurrently. TMZ negatively affects intratumor T cells and macrophages and splenocytes. Addition of MGMT inhibitor O6-benzylguanine (O6-BG), an inactivating pseudosubstrate of MGMT, to TMZ improved survival, but the combination with G47Δ-IL12 did not overcome the antagonistic effects of TMZ treatment on oHSV therapy.Conclusions These results illustrate that chemotherapy can adversely affect oHSV immunovirotherapy. As TMZ is the standard of care for GBM, the timing of these combined therapies should be taken into consideration when planning oHSV clinical trials with chemotherapy for GBM.